Hubungan Tingkat Kecemasan Wanita Pra Menopause Dengan Masa Pra Menopause Di MI Miftakhul Ulum Kabupaten Pasuruan - R.A. Helda Puspitasari; Evy Aristawati (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Pramenopause is 3-10 years before the arrival of menopause, at this stage ovarian hormone production decreases and fluctuates causing various symptoms. The average age in each country is different but around 45 and 55 years, these women will experience changes both physiological and psychological. The general objective of this research is to study the relationship between anxiety levels of pre-menopausal women and pre-menopausal periods. While the specific goal is to identify between the anxiety levels of pre-menopausal women, as well as to identify between pre-menopausal levels and periods. The design of this study used a descriptive method in which the approach was cross sectional, the sample was selected by saturation sampling of 25 people. Data is collected by filling out the questionnaire then the data obtained is then presented in tabular and narrative form. The results showed that the level of anxiety of women in the heavy pre-menopausal period (40%), while those in the moderate category were (36%), while those in the low category were (24%). For symptoms and consequences experienced in the pre-menopausal high as much (76%), and low (24%). The results of the chi square test obtained X 2 count 7.89 and X 2 table 5.991. Because the X 2 count is bigger and the X 2 table is Ho is rejected and H1 is accepted, it means there is a relationship between the pre-menopausal woman's anxiety level and the pre-menopausal periods.Keywords: Pre Menopause, Anxiety, Pra Menopause Steps